The Passage of Time: Unraveling Memory in Clear Light of Day - Muhd. Mustafizur Rahman (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This qualitative research delves into Anita Desai’s Clear Light of Day, focusing on the themes of time and memory and their profound impact on personal and familial identities. Set against the historical backdrop of Old Delhi and the partition of India, the novel explores how time both destroys and preserves, while memory serves as a key element in shaping characters’ psychological experiences and relationships. Through a close textual analysis, the study investigates how Desai intertwines these themes to highlight emotional struggles, alienation, and eventual reconciliation. Drawing on the philosophical insights of T.S. Eliot, who portrays time as both a “Destroyer and Preserver,” the research explores how these forces influence character development and the evolution of family dynamics. The findings underscore the significance of time and memory in the process of emotional healing and self-reconciliation, providing a deeper understanding of the novel’s psychological and thematic complexities.